GIFT-AI: designing generative AI tools for organizational communication - Cruz, Ignacio Fernandez (Frontiers in Communication, 2025)
This article presents a Great Ideas for Teaching (GIFT) activity in which students design and evaluate a custom generative AI (GenAI) tool grounded in organizational communication theory. Working in teams, students identify a workplace communication challenge, apply a relevant theoretical framework, and develop a GenAI prototype to address or improve that process. The assignment is structured around experiential learning principles, encouraging students to learn through iteration, feedback, and reflection. It culminates in an in-class pitch and a documentation guide that outlines the tool’s design, intended use, and ethical implications. By combining theoretical analysis with prompt engineering and design thinking, the activity helps students critically engage with the role of AI in organizational life. It also equips them with practical experience to assess, implement, and communicate the value of AI-mediated communication tools.